MAMMALS RECORDED WITH CAMERA TRAPS IN THE TURISTIC AREA OF THE ALLPAHUAYO-MISHANA NATIONAL RESERVE, LORETO, PERU - COSSIOS, E. Daniel (2022)
The Allpahuayo Mishana National Reserve, located in the Peruvian Amazon, maintains a great biodiversity but, unlike its plants and most groups of vertebrates, its community of large and medium-sized terrestrial mammals has not been the subject of recent evaluations with direct recording methods, with most of these species reported solely from tracks, interviews, or skins and skulls kept by local hunters. In order to have a current list of land mammals in the touristic area of ​​the reserve, we carried out an evaluation with camera traps between May and October 2021. Additionally, we evaluated the diel activity for the eight species that were recorded most than 10 times. 656 independent records of mammals were obtained, corresponding to 19 species identified at least to the genus level, including 17 with terrestrial habits and two mainly arboreal. Several species reported by other authors in different places of the reserve were not captured by our cameras, but we recorded a threatened species that was believed to be extinct in the area: the giant anteater Myrmecophaga tridactyla. The diel activity of the studied species did not show alterations with respect to other publications. Our results suggest that human activities do not alter the diel behavior of the most common mammals in the area, but they can have a negative impact on the total diversity and abundance of certain species, especially large mammals and carnivores.